PENERAPAN HEALTH BELIEF MODEL DALAM MENGANALISIS PERILAKU PENCEGAHAN KECELAKAAN KERJA PADA PEKERJA SUBKONTRAKTOR A PT X PROYEK PEMBANGUNAN JALAN TOL DI KOTA DEPOK TAHUN 2022 - Amanda Puspitawati (2023)
PT X has conducted occupational accident prevention programs such as Safety Talk and Toolbox Meeting, but there are still occupational accident prevention behaviors that are inappropriate. This study aims to see the relationship between workers' perceptions using the Health Belief Model theory with occupational accident prevention behavior. This is quantitative research with a cross-sectional study design using total sampling technique. The population of this study were workers from Subcontractor A, who carried out toll road concreting work as many as 83 workers. Data were collected using a questionnaire given directly to workers. Data analysis included univariate and bivariate using the chi square test. According to the results, it was found that 43 (51.8%) respondents were not good at implementing occupational accident prevention behavior. There is a relationship between the 6 dimensions of the Health Belief Model and occupational accident prevention behavior (p value = 0.000), but the characteristics of respondents, age (p value = 0.061) and education level (p value = 0.319) have no relationship with occupational accident prevention behavior. Thus, to improve respondents perception, knowledge and training can be provided in theory and direct practice repeatedly, and rewards such as providing incentives, also punishments to improve respondents perception. Keywords: Health Belief Model, Behavior, Perception